Still not there where the people are - Andrijašević, Ivana (Teorija in praksa, 2017)
This paper examines Facebook use by local municipal governments in Croatia, focusing on two aspects: municipalities' activities and citizens' engagement. Between 1 October 2016 and 30 November 2016, data from all 428 municipalities in the country were collected and analysed. The key results are that: (1) municipalities' adoption of Facebook is quite modest, with just 153 (35.75%) Croatian municipalities maintaining a Facebook page; (2) municipalities' activity on Facebook is low: during the period under observation on average all municipalities posted 0.39 (SD=0.42) posts per working day, namely 2 posts a week; (3) citizens' engagement is generally low: the average value of popularity is significantly higher than commitment and virality, suggesting that liking is the most popular way citizens interact on Facebook. These findings suggest that Croatian municipalities should make greater efforts to embrace today's new communication tools and step into the digital arena so as to be present where the people are.
Keywords: družbena omrežja; Družbeni mediji; Facebook; Local self-government; Lokalna samouprava; lokalna uprava; Social media